2021
DOI: 10.1016/j.celrep.2021.108710
|View full text |Cite
|
Sign up to set email alerts
|

Lipid molecular timeline profiling reveals diurnal crosstalk between the liver and circulation

Abstract: Highlights d A framework for investigating fasting-feeding cycles and circadian rhythms d Time-series analysis shows molecular oscillations are set by fasting-feeding cycles d In-depth lipidomics provides insights into metabolic crosstalk between tissues d Diurnal regulation of the hepatic PE methylation pathway and lipoprotein secretion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 53 publications
(65 reference statements)
5
29
1
Order By: Relevance
“…Notably, MS ALL analysis is a lipidomics technology that affords high-fidelity identification and accurate quantification of molecular lipid species at a lipidome-wide level using high-resolution tandem mass spectrometry (MS/MS). 45,46 This analysis demonstrated a dose-dependent reduction in CerS2-specific ceramide products with VLCFAs, including Cer d18:1/24:1 and Cer d18:1/24:0 (Figure 2D). In addition, we observed an increase in the long-chain fatty acyl (LCFA)-containing ceramides, including Cer d18:1/16:0, Cer d18:1/ 18:0, and Cer d18:1/14:0.…”
Section: Potent Asos Reduce Cers2 Activitymentioning
confidence: 89%
“…Notably, MS ALL analysis is a lipidomics technology that affords high-fidelity identification and accurate quantification of molecular lipid species at a lipidome-wide level using high-resolution tandem mass spectrometry (MS/MS). 45,46 This analysis demonstrated a dose-dependent reduction in CerS2-specific ceramide products with VLCFAs, including Cer d18:1/24:1 and Cer d18:1/24:0 (Figure 2D). In addition, we observed an increase in the long-chain fatty acyl (LCFA)-containing ceramides, including Cer d18:1/16:0, Cer d18:1/ 18:0, and Cer d18:1/14:0.…”
Section: Potent Asos Reduce Cers2 Activitymentioning
confidence: 89%
“…Unlike yeast cells, a sole methyltransferase, namely PE N -methyltransferase (PEMT), has been thought to be responsible for the PE-to-PC sequential methylation in hepatocytes ( Vance, 2014 ). However, Sprenger et al (2021) recently reported that PMME is highly accumulated in PEMT gene knockout mice, suggesting that, as well as in yeast cells, PE-to-PMME methylation and PMME-to-PC methylation are performed by different methyltransferases in mammalian cells. In mammals, PEMT is mainly expressed in the liver, which serves as the predominant site of PE-to-PC sequential methylation ( Vance, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The metabolism of chylomicron PLs and TAGs after feeding milk fat thus contributes nitrogen bases and PUFAs to both the high PL turnover in the liver and to the lyso-PC formation that transports both fatty acids and nitrogen bases to extrahepatic tissues, including the brain. Recent studies have exemplified that analysis of time courses using stable isotopes ( 156 , 178 ) will clarify the nutritional, diurnal, and developmental regulations of these pathways in the near future.…”
Section: Discussionmentioning
confidence: 99%